Association between Serum Alkaline Phosphatase and Primary Resistance to Erythropoiesis Stimulating Agents in Chronic Kidney Disease: A Secondary Analysis of the HERO Trial - Badve, Sunil V.; Zhang, Lei; Coombes, Jeff S.; Pascoe, Elaine M.; Cass, Alan; Clarke, Philip; Ferrari, Paolo; McDonald, Stephen P.; Morrish, Alicia T.; Pedagogos, Eugenie; Perkovic, Vlado; Reidlinger, Donna; et al. (Canadian journal of kidney health and disease, 2015)
Background: Erythropoiesis stimulating agent (ESA)-resistant anemia is common in chronic kidney disease (CKD). Objectives: To evaluate the determinants of severity of ESA resistance in patients with CKD and primary ESA-resistance. Design: Secondary analysis of a randomized controlled trial (the Handling Erythropoietin Resistance with Oxpentifylline, HERO) Setting and patients: 53 adult patients with CKD stage 4 or 5 and primary ESA-resistant anemia (hemoglobin ≤120 g/L, ESA resistance index [ERI] ≥1.0 IU/kg/week/gHb for erythropoietin or ≥0.005 μg/kg/week/gHb for darbepoeitin, no cause for ESA-resistance identified). Measurements: Iron studies, parathyroid hormone, albumin, liver enzymes, phosphate or markers of oxidative stress and inflammation. Methods: Participants were divided into tertiles of ERI. Multinomial logistic regression was used to analyse the determinants of ERI tertiles. Results: All patients, except one, were receiving dialysis for end-stage kidney disease. The mean ± SD ERI values in the low (n = 18), medium (n = 18) and high (n = 17) ERI tertiles were 1.4 ± 0.3, 2.3 ± 0.2 and 3.5 ± 0.8 IU/kg/week/gHb, respectively (P < 0.001). There were no significant differences observed in age, gender, ethnicity, cause of kidney disease, diabetes, iron studies, parathyroid hormone, albumin, liver enzymes, phosphate or markers of oxidative stress and inflammation between the ERI tertiles. The median [inter-quartile range] serum alkaline phosphatase concentrations in the low, medium and high ERI tertiles were 89 [64,121], 99 [76,134 and 148 [87,175] U/L, respectively (P = 0.054). There was a weak but statistically significant association between ERI and serum alkaline phosphatase (R2 = 0.06, P = 0.03). Using multinomial logistic regression, the risk of being in the high ERI tertile relative to the low ERI tertile increased with increasing serum alkaline phosphatase levels (P = 0.02). No other variables were significantly associated with ERI. Limitations: Small sample size; bone-specific alkaline phosphatase, other markers of bone turnover and bone biopsies not evaluated. Conclusions: Serum alkaline phosphatase was associated with severity of ESA resistance in ESA-resistant patients with CKD. Large prospective studies are required to confirm this association. (Trial registration: Australian New Zealand Clinical Trials Registry 12608000199314)